Inelastic large displacement analysis of thin-walled steel frames - Boonliang Viriyaroj; Usami, Tsutomu; Loo, Yew-Chaye; Wireland, Martin; German Academic Exchange Service (DAAD) (Bangkok : Asian Institute of Technology, 1983)
A finite element formulation in the update d Lagrangian approach is presented for inelastic large is placement analysis of steel frames of thin- walled open cross- section steel frames . A straight beam element with two nodes which contains seven kinematic degrees-of-freedom per node is considered in the analysis. The von Mises's yield criterion and Prandtl-Reuss's stress-strain relationship are employed in the inelastic range. Numerical examples are presented and compared with some available results. Good agreement is observed within the elastic range.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1983
Keywords: Structural frames -- Mathematical models